Effect of ammonium on the hydraulic conductivity of geosynthetic clay liners. Issue 6 (December 2017) - Setz, Melissa C.; Tian, Kuo; Benson, Craig H.; Bradshaw, Sabrina L.
Abstract: Hydraulic conductivity and swell index tests were conducted on a conventional geosynthetic clay liner (GCL) containing sodium-bentonite (Na-B) using 5, 50, 100, 500, and 1000 mM ammonium acetate (NH4 OAc) solutions to investigate how NH4 + accumulation in leachates in bioreactor and recirculation landfills may affect GCLs. Control tests were conducted with deionized (DI) water. Swell index of the Na-B was 27.7 mL/2 g in 5 mM NH4 + solution and decreased to 5.0 mL/2 g in 1000 mM NH4 + solution, whereas the swell index of Na-B in DI water was 28.0 mL/2 g. Hydraulic conductivity of the Na-B GCL to 5, 50, and 100 mM NH4 + was low, ranging from 1.6–5.9 × 10 −11  m/s, which is comparable to the hydraulic conductivity to DI water (2.1 × 10 −11  m/s). Hydraulic conductivities of the Na-B GCL permeated with 500 and 1000 mM NH4 + solutions were much higher (e.g., 1.6–5.2 × 10 −6  m/s) due to suppression of osmotic swelling. NH4 + replaced native Na +, K +, Ca 2+, and Mg 2+ in the exchange complex of the Na-B during permeation with all NH4 + solutions, with the NH4 + fraction in the exchange complex increasing from 0.24 to 0.83 as the NH4 + concentration increased from 5 to 1000 mM. A Na-B GCL specimen permeated with 1000 mM NH4 + solution to chemical equilibrium was subsequently permeated with DI water. Permeation with the NH4 + converted the Na-B to "NH4 -bentonite" with more than 80% of the exchange complex occupied by NH4 + . Hydraulic conductivity of this GCL specimen decreased from 5.9 × 10 −6  m/s to 2.9 × 10 −11  m/s during permeation with DI water, indicating that "NH4 -bentonite" can swell and have low hydraulic conductivity, and that the impact of more concentrated NH4 + solutions on swelling and hydraulic conductivity is reversible.